Phytophthora and Phytopythium species associated with walnut dieback in plantations of northern Patagonia, Argentina - Marfetan, Jorge Ariel; Fernandez, Diana; Gallo, Ana Laura; Vélez, María Laura (Wiley, 2024)
The walnut industry in Argentina has grown in recent years, especially in northern Patagonia. However, this expansion has also brought new challenges, including the emergence of diseases threatening the health and productivity of walnut plantations. One of the most important diseases affecting walnut crops worldwide is ‘ink disease’ or ‘walnut dieback'. The aim of this study was to characterize ink disease, identify the aetiological agents, and estimate its incidence in walnut orchards of northern Patagonia, Argentina. Symptomatic trees were observed in the seven surveyed wal nut orchards, showing a range of symptoms, including chlorosis and wilting, stem cankers and desiccation. In vivo assay and molecular analyses revealed that not only Phytophthora (P.) but also Phytopythium (Ph.) species are the causal agents of the dis ease, with P. drechsleri, Ph. mercuriale and Ph. vexans being the most virulent over the commonly used rootstock Juglans hindsii. Notably, Ph. vexans was the most fre quently isolated pathogen, suggesting its prevalence and potential impact on the re gional walnut industry. Overall, this study provides critical insights into the prevalence and impact of Phytophthora and Phytopythium species on walnut health in northern Patagonia. The presence of multiple pathogenic oomycete species raises concerns about the health of walnut orchards, as well as the potential risk of pathogen trans mission to other fruit crops in the region. The findings will help growers to develop better cultural practices and implement measures to guarantee the sustainability of the walnut industry in Patagonia.